2017
DOI: 10.1038/cddiscovery.2017.27
|View full text |Cite
|
Sign up to set email alerts
|

The bile acid receptor FXR attenuates acinar cell autophagy in chronic pancreatitis

Abstract: The functional relationship between bile acid (BA) and autophagy has not been evaluated in the context of pancreatitis. Here we investigated whether BA and their nuclear farnesoid X receptor (FXR) modulate autophagy and the development of pancreatitis. FXR expression, autophagy, apoptosis and necroptosis were determined in human chronic pancreatitis (CP) tissue in vivo and in pancreatic cells lines in vitro by means of real-time PCR, immunoblots and immunofluorescence. Pancreatic cell lines exposed to the most… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 46 publications
1
20
0
Order By: Relevance
“…Accumulation of bile acid suppresses autophagy in pancreatic acinar cells signals via elevating the expression of nuclear farnesoid X receptor (FXR). FXR diminishes the expression of ATG7 and thereby triggeres inflammation and fibrosis in CP 17 . Besides, tocotrienol-rich fraction activates autophagic death in activated PSCs.…”
Section: Introductionmentioning
confidence: 99%
“…Accumulation of bile acid suppresses autophagy in pancreatic acinar cells signals via elevating the expression of nuclear farnesoid X receptor (FXR). FXR diminishes the expression of ATG7 and thereby triggeres inflammation and fibrosis in CP 17 . Besides, tocotrienol-rich fraction activates autophagic death in activated PSCs.…”
Section: Introductionmentioning
confidence: 99%
“…This mechanism was confirmed in TGR5 ligand ameliorating the immunity of intestinal mucosa in experimental colitis [41]. Moreover, in the pancreas, local accumulation of BAs molecules could inhibit autophagy of pancreatic acinar cells through FXR, leading to the increasing of apoptosis and necrotic apoptosis [42]. Our team previously found that the administration of INT-777 could protect AP in mice and improve pancreatic acinar cell necrosis [43].…”
Section: Discussionmentioning
confidence: 67%
“…This mechanism was confirmed in TGR5 ligand ameliorating the immunity of intestinal mucosa in experimental colitis [41]. Moreover, in the pancreas, local accumulation of BAs molecules could inhibit autophagy of pancreatic acinar cells through FXR, leading to the increasing of apoptosis and necrotic apoptosis [42]. Our team previously found that the administration of INT-777 could protect AP in mice and improve pancreatic acinar cell necrosis [43].…”
Section: Discussionmentioning
confidence: 72%